Colchicine inhibits monosodium urate crystal-mediated inflammation by influencing F-actin formation - Zhu, Lingjiang; Wang, Yuqi; Shan, Lizhen; Xue, Yu; Schett, Georg; Herrmann, Martin; Liu, Lei (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2025)
Objectives: To understand the mechanism by which colchicine inhibits the inflammatory properties of monosodium urate (MSU) crystal deposits and tophi. Methods: We investigated the effects of colchicine on the inflammatory properties of monosodium urate (MSU) crystal deposits in several models: (i) In vitro tophus formation by MSU and neutrophils; (ii) MSU-induced peritonitis model; (iii) Alpha-1-antitrypsin-induced peritoneal MSU flare model; (iv) MSU-induced arthritis model. We measured neutrophil numbers, NET formation, IL-1β production and F-actin generation by MSU crystals. In addition, we tested the effect of actin inhibitors SMIFH2, Cytochalasin B and Latrunculin B in the models. Results: Colchicine did not affect neutrophil numbers in all these models. However, colchicine was highly effective to inhibit NET formation, IL-1β production and F-actin generation indicating less pronounced tophus formation, lower inflammatory properties of tophi and reduced conversion from G-actin into F-actin, respectively. F-actin was shown to accumulate in tophi without presence of colchicine and being resistant to degradation by DNase I. Actin inhibitors SMIFH2 and Cytochalasin B significantly reduced IL-1β and neutrophil elastase levels and mitigated MSU-induced arthritis. Conclusion: Colchicine effects on gout flares are not based on reducing neutrophil numbers but on changing the functional properties of tophi by reducing their DNase-resistant F-actin concentrations and thereby reducing the negative impact of NETs on IL-1β production and the pro-inflammatory state of tophi. Actin inhibitors may be interesting tools to convey anti-inflammatory properties and reduction of flares in gout patients.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Actin; Colchicine; Gout; Monosodium urate crystals; Neutrophil extracellular traps